Perbedaan Angka Kejadian Infeksi Saluran Pernapasan Akut (ISPA) Antara Anak yang Diberi ASI Eksklusif dengan yang Diberi Pengganti ASI (PASI) pada Usia 7-24 Bulan - Dewi, Arum Laksmita, Prof. Dr. Bambang Soebagyo, dr., Sp.A (K) (2017)
Acute Respiratory Tract Infection (ARI) is the main cause of morbidity and mortality infectious disease in the world. ARI is influenced by several factors, such as poor nutrition; indoor air pollution; low birth rate (LBW); population density; the lack of immunization against measles; and the lack of exclusive breastfeeding. Exclusive breastfeeding is very useful for children to prevent infectious disease because breastfeeding has protective substances or immune substances, especially sIgA. This study aims to find out the differences of incidence rate of acute respiratory tract infection (ARI) between children were given exclusive breastfeeding and children were given formula feeding aged 7-24 months. This study used an observational analytic method with Cross Sectional approach, using Cluster Random Sampling. The number of samples is 66 children at Posyandu in Puskesmas Gatak Sukoharjo. Data obtained from questionnaire which analyzed by Chi Square test. In the 33 children were given exclusive breastfeeding, there are 10 children (43,9%) who have a history of ARI. While in the 33 children were given formula feeding, there are 19 children (56,1%) who have a history of ARI. Based on the result of Chi Square test to determine the differences of incidence rate of acute respiratory tract infection (ARI) between children were given exclusive breastfeeding and children were given formula feeding aged 7-24 months, p value <0,05. The incidence rate of ARI is less in the children were given exclusive breastfeeding aged 7-24 months. Keywords: ARI, Exclusive breastfeeding, Formula feeding.